Synthesis, characterisation and olefin oligomerization over nickel, cobalt and zinc substituted synthetic mica montmorillonite - Vogel, Alex Philip (Department of Chemical Engineering, 2016)
Nickel, cobalt and zinc were substituted for structural octahedral aluminium in SMM. X-ray diffraction, together with elemental analysis, confirmed that a 2: 1 layered aluminosilicate had been formed. The inclusion of these metals facilitated the crystallisation of the SMM structure in the synthesis process as was shown by their more well-defined X-ray diffraction patterns over unsubstituted SMM synthesized in this work. The 2: 1 layer spacings increased at nickel contents of 16 and 34wt%, indicating a more montmorillonite-like structure. Cobalt levels at 33wt% were seen to disrupt the basal spacing. The opposite effect was seen with zinc, where increased zinc loadings caused the 2: 1 layers to be drawn closer together. This was indicative of a more micalike structure.